Glacial controls on redox-sensitive trace element cycling in Arctic fjord sediments (Spitsbergen, Svalbard). (15th February 2020) - Herbert, Lisa C.; Riedinger, Natascha; Michaud, Alexander B.; Laufer, Katja; Røy, Hans; Jørgensen, Bo Barker; Heilbrun, Christina; Aller, Robert C.; Cochran, J. Kirk; Wehrmann, Laura M.
Abstract: Glacial meltwater is an important source of bioessential trace elements to high latitude oceans. Upon delivery to coastal waters, glacially sourced particulate trace elements are processed during early diagenesis in sediments and may be sequestered or recycled back to the water column depending on local biogeochemical conditions. In the glaciated fjords of Svalbard, large amounts of reactive Fe and Mn (oxyhydr)oxides are delivered to the sediment by glacial discharge, resulting in pronounced Fe and Mn cycling concurrent with microbial sulfate reduction. In order to investigate the diagenetic cycling of selected trace elements (As, Co, Cu, Mo, Ni, and U) in this system, we collected sediment cores from two Svalbard fjords, Van Keulenfjorden and Van Mijenfjorden, in a transect along the head-to-mouth fjord axis and analyzed aqueous and solid phase geochemistry with respect to trace elements, sulfur, and carbon along with sulfate reduction rates. We found that Co and Ni associate with Fe and Mn (oxyhydr)oxides and enter the pore water upon reductive metal oxide dissolution. Copper is enriched in the solid phase where sulfate reduction rates are high, likely due to reactions with H2 S and the formation of sulfide minerals. Uranium accumulates in the solid phase likely following reduction by both Fe- and sulfate-reducing bacteria, while Mo adsorbs to Fe and Mn (oxyhydr)oxides in the surface sediment and is removed from the pore water at depth where sulfidization makes it particle-reactive. Arsenic is tightly coupled to Fe redox cycling and its partitioning between solid and dissolved phases is influenced by competition with FeS for adsorption sites on crystalline Fe oxides. Differences in trace element cycling between the two fjords suggest delivery of varying amount and composition of tidewater glacier (Van Keulenfjorden) and meltwater stream (Van Mijenfjorden) material, likely related to oxidative processes occurring in meltwater streams. This processing produces a partially weathered, more reactive sediment that is subject to stronger redox cycling of Fe, Mn, S, and associated trace elements upon delivery to Van Mijenfjorden. With climate warming, the patterns of trace element cycling observed in Van Mijenfjorden may also become more prevalent in other Svalbard fjords as tidewater glaciers retreat into meltwater stream valleys.